AB0716 SEX DIFFERENCES IN CLINICAL PHENOTYPE AND RADIOGRAPHIC DISEASE PROGRESSION IN AXIAL SPONDYLOARTHRITIS: RESULTS FROM THE GERMAN SPONDYLOARTHRITIS INCEPTION COHORT. (2nd June 2020) - Protopopov, M.; Torgutalp, M.; Sieper, J.; Haibel, H.; Proft, F.; Rios Rodriguez, V.; Rudwaleit, M.; Poddubnyy, D.
Abstract : Background: It is presumed that the phenotype of the axial spondyloarthritis (axSpA) may differ in females and males; the published data are controversial. Objectives: To explore the sex differences in disease features and radiographic progression in axSpA. Methods: A total of 210 patients with axSpA (115 with radiographic and 95 with non-radiographic axSpA) were selected for analysis. Spinal radiographs were scored by two readers in a random order according to the modified Stoke Ankylosing Spondylitis Spinal Score (mSASSS). Pelvic radiographs were scored according to the grading system of the modified New York criteria; a sacroiliitis sum score was calculated as a sum of the grades for both sacroiliac joints. Mann-Whitney and Fisher exact tests were performed for group comparisons. A multivariable regression analysis was performed to analyze the influence of gender on radiographic progression. Results: Males (n=107; 51%) were significantly younger at disease onset (34.8 ± 10.3 vs. 31.5 ± 11.2 years, p=0.008) and at diagnosis (37.5 ± 10.2 vs. 34.1 ± 11.2 years, p=0.006); symptom duration at baseline was similar (4.1 ± 2.6 vs. 4.3 ± 2.8 years, p=0.66). Females were less often HLA-B27 positive (74 (72.5%) vs. 92 (86.0%), p=0.02), had higher baseline disease activity (BASDAI 4.3±2.2 vs 3.7±2.0; p=0.05), but lower baseline C-reactive protein level (7.1 ± 10.9 vs. 12.3 ±18.2 mg/l, p=0.08), and similar time-averaged ASDAS (2.5±0.8 vs 2.4±1.0; p=0.385). Males more frequently had definite radiographic sacroiliitis (70.1% vs. 38.8%; p<0.001), higher sacroiliitis sum score (4.9 ±1.9 vs 3.2±1.8, p<0.001), and higher mean mSASSS (6.1 ± 10.7 vs 2.4 ± 4.0; p=0.100) at baseline. Other variables were comparable between the groups. There was a trend for a higher radiographic progression in males in all explored outcomes, statistically significant only for the formation/progression of syndesmophytes (23 (21.5%) vs. 10 (9.7%), p=0.023), with no differences in the radiographic progression of sacroiliitis. In a multivariate logistic regression analysis, similar odds for spinal radiographic progression, new syndesmophyte formation and radiographic progression of sacroiliitis by ≥1 grade were seen – Table 1 . Conclusion: There was a trend for male patients to have more radiographic damage at the baseline and more progression after two years, as reflected by the percentage of patients with new syndesmophytes. : Acknowledgments: GESPIC has been financially supported by the German Federal Ministry of Education and Research (BMBF). As funding by BMBF was reduced in 2005 and stopped in 2007, financial support has been obtained from Abbott / Abbvie, Amgen, Centocor, Schering-Plough, and Wyeth. Since 2010 GESPIC is supported by Abbvie. Dr. Murat Torgutalp was supported by the Scientific and Technological Research Council of Turkey (TUBITAK). Disclosure of Interests: Mikhail Protopopov Consultant of: Novartis, Murat Torgutalp: None declared, Joachim Sieper Consultant of: AbbVie, Boehringer Ingelheim, Eli Lilly and Company, Janssen, Merck, Novartis, Pfizer, Roche, and UCB Pharma, Speakers bureau: AbbVie, Boehringer Ingelheim, Eli Lilly and Company, Janssen, Merck, Novartis, Pfizer, Roche, and UCB Pharma, Hildrun Haibel Consultant of: Abbvie, Jansen, MSD, and Novartis, Speakers bureau: Abbvie, Jansen, MSD, and Novartis, Fabian Proft Grant/research support from: Novartis Pharma GmbH, Consultant of: Consultancy / speaker fees from: Abbvie, BMS, Celgene, Lilly, MSD, Novartis, Pfizer, Roche, UCB, Speakers bureau: Consultancy / speaker fees from: Abbvie, BMS, Celgene, Lilly, MSD, Novartis, Pfizer, Roche, UCB, Valeria Rios Rodriguez Consultant of: Abbvie, Novartis, Martin Rudwaleit Consultant of: AbbVie, BMS, Celgene, Janssen, Eli Lilly, MSD, Novartis, Pfizer, Roche, UCB Pharma, Denis Poddubnyy Grant/research support from: AbbVie, MSD, Novartis, and Pfizer, Consultant of: AbbVie, Bristol-Myers Squibb, Eli Lilly, MSD, Novartis, Pfizer, Roche, UCB, Speakers bureau: AbbVie, Bristol-Myers Squibb, Eli Lilly, MSD, Novartis, Pfizer, Roche, UCB